Veering Off the Abolitionist Path in America: The Influence of the Ambiguously Written Constitution - Samarth, Avinash (2017)
In the 21st century, capital punishment in the United States stands as a peculiar institution. Despite widespread international movements for its abolition, and widespread expert agreement on its ills, the death penalty still persists in the United States. America remains the only country in the Western world to retain the death penalty today. We use it frequently, executing approximately 52 people per year, a rate comparable to both Saudi Arabia and Yemen. The question of why the United States still retains the death penalty has been the subject of debate for decades. Countless historical explanations have been posited, ranging from the religious to the political, from the racial, to the legal. The historical analysis of modern social institutions is important -- they help us understand why and how such institutions came to be normatively accepted and persistent in the world today. In this paper I will set out to examine why the United States retained the death penalty despite its initial suspension in 1972 by the Supreme Court under Furman v. Georgia. In doing so I will relate the narratives of two countries, the United States and the United Kingdom, and their experience with abolition in the post-World War II era